Fast algorithms for H.264 encoding and transcoding - Ye, Tianxiao (2009)
In this thesis, several fast algorithms related to H.264/AVC, the latest and most advanced video standard, are explored. The first part of this work is focused on using SAD information to achieve early detection of all-zero blocks such that the complexity for coding these blocks can be avoided. A new mathematical model is introduced and an efficiency detection method is derived. The second part of this work is focused on using Hadamard transform information to achieve all-zero block detection, when SAD information is not available. A novel approach is proposed based on the relationship between integer transform and Hadamard transform. The final part of this work is focused on transcoding. Two fast algorithms are proposed to speed up the H.263 to H.264 inter frame transcoding. Experimental results show that the proposed algorithms can reduce the complexity of H.264 encoding and transcoding, while maintaining a similar video quality.